Peranan Guru dalam Meningkatkan Keaktifan Peserta Didik Melalui Media Audio Visual Pada Mata Pelajaran PPKN di Kelas XI SMK Negeri 2 Penyabungan Tahun Ajaran 2022/2023 - Edi Dardi; Corry Corry; Mariah S.M. Purba (Journal on Education, 2023)
This study aims to examine the teacher's role as educator, facilitator, and motivator in increasing student activity through audio-visual media in Civics subjects in Class XI SMK Negeri 2 Penyabungan in the 2022/2023 academic year. This research was conducted at SMK Negeri 2 Penyabung, and used Civics teachers as resource persons to support data acquisition in this study. This research was conducted from February to the second week of March 2023. Data collection was carried out through gathering information by observing and checking into the classroom when the teacher was teaching using audio-visual media and then adding in-depth questions to further strengthen the results of the research data. From this study it was found that the role of the teacher as an educator in increasing the activity of students through Audio Visual learning media in PKn subjects at SMK Negeri 2 Panyabungan was carried out by providing a fair attitude for students in using audio visual media and having a strong mentality in dealing with participants. students who are taught, have extensive knowledge in educating students properly, and always provide good examples or examples to students in using learning media in the classroom; The role of the teacher as a facilitator in increasing the activity of students through learning media in Civics subjects at SMK Negeri 2 Penyabung, namely by providing audio-visual media that can attract the attention of students so that students' interest in learning becomes higher, and the role of the teacher as a motivator in increasing the activeness of students through learning media in Civics subjects at SMK Negeri 2 Panyabungan, namely the teacher always provides direction and encouragement so that students' interest in learning in using audio-visual media becomes more effective.